The Influence of Education Level, Job Satisfaction, and Compensation on the Performance of State Civil Apparatuses at the Mambi District Office - Dwyki Suhasdi; Rina; Andi Hendra Syam (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
The purpose of this study was to analyze the effects of educational attainment, job satisfaction, and compensation on the performance of government private institutions in Mambi District Office, Mamasa District, West Sulawesi Province. It was to analyze the impact. Compensation for the performance of state private agencies in the Mambi district office. The analytical method used in this study is multiple regression analysis. Survey data were obtained from the State Civil Affairs Organization of the Mambi District Office of a total of 55 individuals. The research approach is causal and descriptive in character. The results of this study show that:1) Education level has been shown to have a significant positive impact on ASN performance. H. The higher the level of education, the higher the level of performance of ASNs in the Mambi district office. 2) Job satisfaction has been shown to have a significant positive impact on ASN performance. In other words, the more ASN is satisfied with the results of her work, the better her ASN will perform in the Mambi district office. 3) Rewards have been shown to have a positive and significant impact on ASN performance. That is, the better the compensation, the higher the level of performance, the higher the level of performance of his ASN in the Mambi district office, and the higher the level of 4). Education, job satisfaction, and compensation have all been shown to have a significant positive impact on ASN performance. That is, the higher the level of education, the higher the level of performance due to the results of one's work and the provision of appropriate rewards. Also, his ASN in Mambi District Office is high.